Ablative therapy in oligometastatic non-small cell lung cancer—an editorial on recent evidence - Niglas, Mark; Cheung, Patrick (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Lung cancer is the leading cause of cancer-related mortality, and will account for 26% of all cancer deaths in 2017 (1). With approximately 40% of all patients diagnosed with non-small cell lung cancer (NSCLC) presenting with stage IV disease (2), the optimal management of metastatic disease is an important question. In patients with oligometastatic NSCLC, often defined as 1 to 3 or 1 to 5 sites of metastatic spread, there is significant controversy in treatment approach (3).